AnMBR as alternative to conventional CSTR to achieve efficient methane production from thermal hydrolyzed sludge at short HRTs. (15th September 2018) - Wandera, Simon M.; Qiao, Wei; Jiang, Mengmeng; Gapani, Dalal E.; Bi, Shaojie; Dong, Renjie
Abstract: An anaerobic membrane reactor (AnMBR) was investigated and compared with a continuously stirred tank reactor (CSTR) in order to treat thermal hydrolyzed sludge. Long term experiments were carried out by shortening the hydraulic retention time (HRT) from 30 d to 3 d under mesophilic conditions. The results obtained show that at each HRT the AnMBR had higher removal efficiencies for total solids and volatile solids, and higher specific methanogenic activities. Comparable process stability was obtained for the two reactors. A flat sheet membrane could work with the high solid system but the trans-membrane pressure appeared sensitive to total solid concentrations. Foaming occurred in the AnMBR at a HRT of 3 d, and an organic loading rate of 8.84 kg-COD/(m 3 ·d) further deteriorated the membrane filtration. Hydrogentropic methanogens, in particular Methanospirillum, dominated the archaea community in both the AnMBR and the CSTR at a HRT of 3 d (i.e. 85% in the AnMBR and 95% in the CSTR). An obligate acetoclastic methanogen, Methanosaeta, was found at a very low level during all the HRTs. As a whole, the efficiency of methanogenesis in the AnMBR to treat thermal hydrolyzed sludge was proved to be better than in the CSTR during short HRTs. Highlights: The efficiency of methanogenesis in the AnMBR was better than in the CSTR. Hydrogentrophic methanogens dominate the two reactors at short HRT. The trans-membrane pressure appeared sensitive to total solid concentrations. Foaming occurred in AnMBR deteriorated the membrane filtration.